2017
DOI: 10.1097/md.0000000000005766
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of TERT promoter mutation and telomere length in hepatocellular carcinoma

Abstract: Promoter mutations in telomerase reverse transcriptase (TERT) and telomere length have been studied in various tumors. In the present study, the frequency and clinical characteristics of TERT promoter mutation and telomere length were studied in hepatocellular carcinoma (HCC). TERT promoter mutation and telomere length were analyzed in 162 tumor samples of the patients with HCC by sequencing and real-time PCR, respectively. The TERT promoter mutation rate was 28.8% (46/160) in HCC and was associated with males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 29 publications
(35 reference statements)
3
35
4
Order By: Relevance
“…However, we found no evidence that SNP rs401681 is associated with mean TL or TERT mutation. In our previous study, we found that ALT level and TL were significantly related 9. But in this study, aspartate transaminase and ALT were not associated with TERT -CLPTM1 locus polymorphism.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…However, we found no evidence that SNP rs401681 is associated with mean TL or TERT mutation. In our previous study, we found that ALT level and TL were significantly related 9. But in this study, aspartate transaminase and ALT were not associated with TERT -CLPTM1 locus polymorphism.…”
Section: Discussioncontrasting
confidence: 71%
“…Also, TL might have a potential value as a prognostic factor in HCC. According to many reports, while shortened tumor TL shows poorer prognosis in most solid tumors, HCC has been observed with favorable prognosis as in colorectal cancer 1,9…”
Section: Discussionmentioning
confidence: 99%
“…The results showed HBV integrations in 24%-30% of male patients with HCC but only in 12%-17% of female patients with HCC (20)(21)(22) ; -124A>G TERT promoter mutation was identified in 32%-33% of male patients with HCC but only in 15%-24% in female patients with HCC. (23,24) Though the sample size of female patients with HCC included in these studies was usually small (fewer than 10 cases), the results did support an enrichment of HBV insertions and TERT promoter mutations in male patients with HCC. Therefore, a mechanism for such genetic changes might exist to induce TERT expression predominantly in hepatocytes from male, but not female, patients.…”
Section: Discussionmentioning
confidence: 76%
“…Interestingly, shorter telomeres are observed more frequently (telomere length ratio between HCC and surrounding tissues lower than the mean, 70.1% versus higher, 29.9%) in HCC that is not related to hepatitis B (50.0% versus 50.0%) or C (60.0% versus 40.0%), or alcohol abuse (50.0% versus 50.0%), although the difference does not reach statistical significance [83]. Telomere shortening can be detected in peripheral blood.…”
Section: Liver Cirrhosis -Update and Current Challengesmentioning
confidence: 90%
“…Early liver carcinogenesis is associated with telomere shortening, while disease progression is associated with telomere extension, cell immortalisation and reactivation of telomerase [83]. Longer telomeres in HCC are associated with higher stage (regional or distant spread versus localised tumour) and grade (III-IV versus lower grade) as well as with worse survival [83,84]. Telomerase promotes HCC development via several pathways, not limited to maintenance of telomeres and thus cellular proliferation.…”
Section: Liver Cirrhosis -Update and Current Challengesmentioning
confidence: 99%